Large-Signal Stability Analysis of a Modular Multilevel Converter Based on Mixed Potential Theory - Hanhang Yin; Qianming Xu; Xiaoping Zhou; Xucheng Huang; Lei Wang; Zhikang Shuai; Josep M. Guerrero (CSEE Journal of Power and Energy Systems)
Modular multilevel converters (MMC) have been widely applied in high voltage direct current (HVDC) transmission systems, while complex dynamic characteristics pose challenges for stable operation under large-signal disturbance. In this paper, large-signal stability of MMC is investigated under grid voltage and power disturbances based on mixed potential function (MPF). First, an MMC simplified model based on average value model (AVM) is introduced. Then, the physical mechanism of large-signal instability phenomenon is revealed for MMC. Based on the simplified model, large-signal stability of MMC is analyzed by applying MPF. Furthermore, to diminish the conservatism of MPF, a large-signal stability criterion is defined by introducing a conservative correction factor. The influences of system parameters on large-signal stability of MMC are presented by the region of asymptotic stability (RAS). Finally, PLECS simulation case studies are carried out to verify the proposed stability criterion under grid voltage and power disturbances.